Respostas
respondido por:
1
Vamos lá.
∆=b²-4.a.c
a=1 b=-35 c=150
∆=(-35)²-4.1.150
∆=1225-4.1.150
∆=1225-600
∆=625
x= -b ± ✓∆ / 2.a
x= -(-35) ± ✓625 / 2.1
x= 35 ± 25 / 2
x'= 35 + 25 / 2
x'= 60 / 2
x'= 30
x''= 35 - 25 / 2
x''= 10 / 2
x''= 5
S = ( 5 ; 30 )
;)
∆=b²-4.a.c
a=1 b=-35 c=150
∆=(-35)²-4.1.150
∆=1225-4.1.150
∆=1225-600
∆=625
x= -b ± ✓∆ / 2.a
x= -(-35) ± ✓625 / 2.1
x= 35 ± 25 / 2
x'= 35 + 25 / 2
x'= 60 / 2
x'= 30
x''= 35 - 25 / 2
x''= 10 / 2
x''= 5
S = ( 5 ; 30 )
;)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás